OCA : Oracle 10g administration I : study guide - Dawes, Chip (SYBEX, 2005)
Here's the book you need to prepare for the Oracle Database 10g Administration I exam, 1Z0-042. This Study Guide was developed to meet the exacting requirements of today's Oracle certification candidates. In addition to the consistent and accessible instructional approach that has earned Sybex the ""Best Study Guide"" selection in CertCities Readers Choice Awards for two consecutive years, this book provides:Clear and concise information on database administration with Oracle 10gPractical examples and insights drawn from the authors' real-world experiencesLeading-edge exam prep